Distensibility and Strength of the Pelvic Floor Muscles of Women in the Third Trimester of Pregnancy. (28th April 2014) - Petricelli, Carla Dellabarba; Resende, Ana Paula Magalhães; Elito Júnior, Julio; Araujo Júnior, Edward; Alexandre, Sandra Maria; Zanetti, Miriam Raquel Diniz; Nakamura, Mary Uchiyama
Abstract : Objective. The objective of this study was to compare the role of the pelvic floor muscles between nulliparous and multiparous women in the third trimester of pregnancy, by analyzing the relationship between electrical activity (surface electromyography—EMG), vaginal palpation (modified Oxford scale), and perineal distensibility (Epi-no). Methods. This was an observational cross-sectional study on a sample of 60 healthy pregnant women with no cervical dilation, single fetus, gestational age between 35 and 40 weeks, and maternal age ranging from 15 to 40 years. The methods used were bidigital palpation (modified Oxford scale, graded 0–5), surface EMG (electrical activity during maximal voluntary contraction), and perineal distensibility (Epi-no device). The Pearson correlation coefficient (r ) was used to analyze the Epi-no values and the surface EMG findings. The Kruskal-Wallis test was used to compare the median values from surface EMG and Epi-no, using the modified Oxford scale scores. Results. Among the 60 patients included in this study, 30 were nulliparous and 30 multiparous. The average maternal age and gestational age were 26.06 (±5.58) and 36.56 (±1.23), respectively. It was observed that nulliparous women had both higher perineal muscle strength (2.53 ± 0.57 versus 2.06 ± 0.64 ; P = 0.005 ) and higher electrical activity (45.35 ± 12.24 μ V versus 35.79 ± 11.66 μ V; P = 0.003 ), while among the multiparous women, distensibility was higher (19.39 ± 1.92 versus 18.05 ± 2.14 ; P = 0.013 ). We observed that there was no correlation between perineal distensibility and electrical activity during maximal voluntary contraction (r = - 0.193 ; P = 0.140 ). However, we found a positive relationship between vaginal palpation and surface electromyography (P = 0.008 ), but none between Epi-no values (P = 0.785 ). Conclusion. The electrical activity and muscle strength of the pelvic floor muscles of the multiparous women were damaged, in relation to the nulliparous women, while the perineal distensibility was lower in the latter group. There was a positive relationship between surface EMG and the modified Oxford scale.